2023
DOI: 10.1101/2023.02.10.526562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recruitment of apolipoprotein E facilitates Herpes simplex virus 1 attachment, entry, and release

Abstract: Over two decades, epidemiological studies have revealed that interactions between human polymorphic apolipoprotein 4 (ApoE, isoform 4) and herpes simplex virus type 1 (HSV1) associate with higher risk of Alzheimer's disease, a serious and increasing issue among elder populations worldwide. Nevertheless, little is known about the mechanisms behind ApoE-HSV1 interactions at molecular levels. Here, we investigate the effects of ApoE on the HSV1 infectious life cycle in in vitro cell experiments. Analysis of HSV1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…In the study using APOE4 knockout mice, Burgos et al (2006) detected significant lower HSV-1 genomes in the nervous system than that in the wildtype mice, suggesting that APOE4 facilitates HSV-1 invasion and latency establishment in the brain. Later, by examining key steps of HSV-1 lytic replication, Liu et al (2023) surprisingly demonstrated that APOE4 protein inhibits HSV-1 attachment but not viral entry, replication, assembly, or intracellular transportation of lytic replication, which may contribute to the enhanced latency. Paradoxically, APOE4 can be incorporated into HSV-1 virions to promote viral release from cell membrane ( Liu et al, 2023 ).…”
Section: Apoe4 and Other Genetic Risk Factors Are Not Only Associated...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study using APOE4 knockout mice, Burgos et al (2006) detected significant lower HSV-1 genomes in the nervous system than that in the wildtype mice, suggesting that APOE4 facilitates HSV-1 invasion and latency establishment in the brain. Later, by examining key steps of HSV-1 lytic replication, Liu et al (2023) surprisingly demonstrated that APOE4 protein inhibits HSV-1 attachment but not viral entry, replication, assembly, or intracellular transportation of lytic replication, which may contribute to the enhanced latency. Paradoxically, APOE4 can be incorporated into HSV-1 virions to promote viral release from cell membrane ( Liu et al, 2023 ).…”
Section: Apoe4 and Other Genetic Risk Factors Are Not Only Associated...mentioning
confidence: 99%
“…Later, by examining key steps of HSV-1 lytic replication, Liu et al (2023) surprisingly demonstrated that APOE4 protein inhibits HSV-1 attachment but not viral entry, replication, assembly, or intracellular transportation of lytic replication, which may contribute to the enhanced latency. Paradoxically, APOE4 can be incorporated into HSV-1 virions to promote viral release from cell membrane ( Liu et al, 2023 ). These findings indicate that APOE4 has distinct function in various steps of HSV-1 lytic replication, although the discrepancies remain unexplained.…”
Section: Apoe4 and Other Genetic Risk Factors Are Not Only Associated...mentioning
confidence: 99%
See 1 more Smart Citation